Ultrasonography of the Kidneys in Healthy and Diseased Camels (Camelus dromedarius) - Mohamed Tharwat (Veterinary Medicine International)
This review article is written to describe the results of ultrasonography of the kidneys in healthy camels as well as camels with some renal disorders. In the dromedary camel, the physiology of the kidney is of interest in view of the specialization of the camel to hot dry deserts and to prolonged periods without water. It plays an important role in water conservation through the production of highly concentrated urine that may predispose animal to varieties of renal disorders. Examples of kidney affections in dromedary camels are renal capsular pigmentation, medullary hyperemia, subcapsular calcification, cortical and medullar discoloration, hemorrhage in renal pelvis, nephrolithiasis, and hydatidosis. Congestion, hemorrhage, hydronephrosis, acute glomerulonephritis, subacute glomerulonephritis, chronic glomerulonephritis, diffuse interstitial nephritis, focal interstitial nephritis, renal cyst, hyaline degeneration, renal amyloidosis, tubular nephrosis, pyelonephritis, hemosiderosis, and renal toxicity. When the kidney is examined by ultrasonography, the clinician can get sufficient information about the size, position, and echo patterns of the renal cortex and medulla and renal pelvis and outlines of the renal blood vessels. In recent years, ultrasonography has been used in camels for scanning of the healthy status as well as evaluation and determining the diagnosis and prognosis of diseased cases. Examples of diseases evaluated by ultrasonography are paratuberculosis, trypanosomiasis, pneumonia, pleurisy, gastrointestinal neoplasms, chronic peritonitis, splenic abscessation, and hepatic disorders. Of the renal disorders assessed by ultrasonography are nephrolithiasis, hydronephrosis, pyelonephritis, renal abscessation, and renal neoplasms. Ultrasound guidance in biopsy of renal specimens has also been reported in dromedary camels.